Imagining the creator God from antiquity to astrophysics - De Schrijver, Georges (Ateneo de Manila University Press, 2015)
Ever since it was demonstrated in the 1920s that the universe, with its trillions of galaxies, is caught up in a process of steady expansion, it became evident that it must have originated from an "initial singularity," a "Big Bang," which gave rise to the formation of subatomic parts, atoms, molecules, cloud of gas, and finally, stars and galaxies. Running this expansion back in time, scientists began to reckon with the miracle of an evolving universe of which we are the outcome: the iron in our blood has been formed in the stars. This book gives an overview of the cosmologies that we are in vogue in antiquity - The Jewish and Christian concepts of creation, and the classical thinkers in Greek cosmology: Plato, Aristotle, and Ptolemy - and in modern times, Copernicus, Galileo, Kepler, and Newton. The book brings us right down to the present day with a careful and readable treatment of the scientific innovations inaugurated by Einstein and the specialist in quantum physics, and to recent developments in astrophysics. This path of exploration opens the avenue for imagining a Creator God who is so generous that he invites creation to share in his own creativity.